(3cjajI QSe GdOSJhQ hhVY eG jMJGL Edjg debhe GdbeQ dSfI cGedIs - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3hHYO , gPg hQbGJ ai cjajI QSe GdOSJhQ hhVY eG jMJGL ajg debhe GdbeQ dSfI cGedI s
(3BNQgG (B:s
(3hjchf GdSWQ GdChd ef GdOSJhQ ddSfI GdeaQhVI HeG ajg ef GdhSW hGdNGUI hGdeQcR hGdCjGe hGdYdGeI gh HbjI eG ai GdSWQ ef GdOSJhQ ef GdSfI GdMGdjI hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HBNQgG LOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B128 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B158 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 - (3U (B204 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B125) s
Keywords: (3Gdadcs